Desain Kemasan Rappo dalam Membangun Cita-Cita Identitas Merek - Ramayanti, Dwi; Swatriani, Rinkapati (Universitas Komputer Indonesia, 2025)
Rappo is a local brand that produces products, especially bags. A social enterprise that produces recycled plastic bag waste (kresek) that is designed in such a way that it becomes a product that has a selling value. Conceptually, a brand means a